The Changing Material Conditions of Cameroonian Migrants in South Africa: What does this say about an â€œAfrophobicâ€ post-apartheid State? (African Human Mobility Review, 2021)
Violent attacks on African migrants have produced a richer body of knowledge onAfrican transnational migration, xenophobia/Afrophobia, and their intersections withquestions of citizenship and autochthony, especially in a country that historically hasalways been a home for African migrants. Constellations of narratives now vilify SouthAfrica as a demonic state whose hatred of Africans and fixation on exorcising themhave short-circuited the process of nation-building. The vilification of South Africaalso tells us that many researchers, scholars, and even migrants are unaware of the waysthat the country has transformed the lives of its increasing African migrant population.This article reflects on the changing material conditions of Cameroonians in SouthAfrica to understand why this â€œAfrophobicâ€ state is still a key migration destinationfor Cameroonians. Drawing on personal exilic experiences, observations, and relevantliterature, we argue that despite the victimization of Africans, including Cameroonians,this constitutional democracy has opened up political, economic and socioculturalopportunities for many Cameroonians residing permanently in the country. Inforging this argument, the article interrogates the political landscape in Cameroonand examines key economic and sociocultural moments/activities in South Africa aswell as accomplishments in this migrant community, to elicit how access to differentopportunities in South Africa has significantly transformed the lives of Cameroonians.